GIS integrated RUSLE model-based soil loss estimation and watershed prioritization for land and water conservation aspects - Singh, Mahesh Chand; Sur, Koyel; Al-Ansari, Nadhir; Arya, Prashant Kumar; Verma, Vipan Kumar; Malik, Anurag (Frontiers in Environmental Science, 2023)
Land degradation has become one of the major threats throughout the globe, affecting about 2.6 billion people in more than 100 countries. In India, land degradation has affected about 105.48 million hectares. Thus, modeling and mapping soil loss, and assessing the vulnerability threat of the active erosional processes in a region are the major challenges from the land and water conservation aspects. The present study attempted rigorous modeling to estimate soil loss from the Banas Basin of Rajasthan state, India, using GIS-integrated Revised Universal Soil Loss Equation (RUSLE) equation. Priority ranking was computed for different watersheds in terms of the degree of soil loss from their catchments, so that appropriate conservation measures can be implemented. The total area of Banas basin (68207.82km2) was systematically separated into 25 watersheds ranging in area from 113.0 to 7626.8km2. Rainfall dataset of IMD for 30 years (1990-2020), FAO based Soil map for soil characterization, ALOS PALSAR DEM for topographic assessment, and Sentinal-2 based land use and land cover (LULC) map were integrated for modeling and mapping soil erosion/loss risk assessment. The total annual soil loss in the Banas basin was recorded as 21766048.8 tons. The areas under very low (0-1 t.ha-1.year-1), low (1-5 t.ha-1.year-1), medium (5-10 t.ha-1.year-1), high (10-50 t.ha-1.year-1) and extreme (>50 t.ha-1.year-1) soil loss categories were recorded as 24.2, 66.8, 7.3, 0.9 and 0.7%, respectively, whereas the respective average annual soil loss values were obtained as 0.8, 3.0, 6.0, 23.1 and 52.0 t.ha-1.year-1. The average annual soil loss among different watersheds was recorded in the range of 1.1-84.9 t.ha-1.year-1, being highest (84.9 t.ha-1.year-1) in WS18, followed by WS10 (38.4 t.ha-1.year-1), SW25 (34.7 t.ha-1.year-1) and WS23 (17.9 t.ha-1.year-1), whereas it was lowest for WS8 (1.1 t.ha-1.year-1). Thus, WS18 obtained the highest/top priority rank in terms of the average annual soil loss (84.9 t.ha-1.year-1) to be considered as the first priority for land and water conservation planning and implementation. The quantitative results of this study would be useful for the implementation of land and water conservation measures in the problematic areas of the Banas basin for controlling soil loss through water erosion.